Non-adherence to anti-tuberculosis treatment and determinant factors during intensive phase treatment of pulmonary tuberculosis - Saimi Saimi; Nursini Juiban Hadi (Malahayati International Journal of Nursing and Health Science, 2024)
Background: The number of Tuberculosis (TB) sufferers in various regions is still high. Efforts to reduce tuberculosis rates carried out by the health service have not produced much results. One of the factors that determines the recovery of TB patients is compliance in taking anti-tuberculosis medication. Tuberculosis sufferers who do not comply with taking intensive phase medication according to the dosage rules set by health workers can develop drug resistance or rifampicin resistance, so the chance of being cured is smaller.Purpose: To determine factors of non-adherence to anti-tuberculosis treatment during intensive phase treatment of pulmonary tuberculosisMethod: This research uses cross-sectional research. This method is used to examine the relationship between one or more dependent variables and one or more independent variables at a certain time, in this case variables related to patient compliance in the intensive phase of TB treatment. The subjects in this study were 53 patients suffering from pulmonary TB in the working area of the Aikmel Community Health Center, East Lombok. The research sample was selected using the total sampling method. Data collection uses interviews and questionnaires. Data analysis in cross-sectional research involves several steps to describe and interpret the characteristics or variables observed at a particular point in time.Results: The variables education level, attitude and age have a significant relationship with adherence to taking anti-tuberculosis drugs in the intensive phase. In the education variable, the p-value (Significance Value): 0.008, Relative Influence (PR): 5.989 and Confidence Interval (CI): 1.602 – 22.389, in the attitude variable p-value: 0.038, Relative Influence (PR): 3.473, Interval Confidence (CI): 1.074 – 11.226 and p-value: 0.039, Relative influence (PR) 3.943 and Confidence Interval (CI): 1.075 – 14.468. For the variables Gender, Occupation, Side Effects of Drugs, Role of Health Workers, and Role of Drug Swallowing Supervisor, there is no significant relationship between these variables and adherence to taking anti-TB drugs in the intensive phase.Conclusion: Based on the research findings, the conclusion that can be drawn is that low education, a supportive attitude, and older age can be significant risk factors for non-adherence to taking intensive phase anti-TB drugs in pulmonary TB patients in the Aikmel Health Center area. The variables gender, occupation, drug side effects, health worker role, and therapeutic drug monitoring (TDM) role did not have a significant relationship. Therefore, intervention strategies and public health approaches can be focused on these risk groups to increase the level of compliance in taking intensive phase anti-TB drugs.